Predictors of Postpartum Hemorrhage and Associated Outcomes at a Midwest Academic Medical Center - Megan Mooberry; Natalie Voss; Linder Wendt; Kimberly A. Kenne; J. Brooks Jackson; Mary B. Rysavy (Women's Health Reports)
Background: Postpartum hemorrhage (PPH) remains a significant cause of maternal morbidity and mortality around the world, with rates increasing in the United States. The objective of this study was to determine predictors of, and outcomes associated with, PPH at a Midwest academic health center. Methods: Demographic and clinical data were obtained from the electronic medical record on all consecutive delivering patients between May 1, 2020, and April 30, 2021. Associations between PPH and perinatal characteristics and outcomes were assessed using logistic regression models. A significance threshold of 0.05 was used for all comparisons. Results: Of the 2497 delivering patients during the study period, 437 (18%) experienced PPH. Chronic hypertension, gestational hypertension, and preeclampsia with and without severe features were all associated with increased odds of PPH (odds rations [ORs], respectively, 1.61 (95% CI:1.13–2.24, p = 0.006), 1.62 (95% CI 1.18–2.21, p = 0.003), 1.81 (95% CI 1.14–2.80, p ≤ 0.001), and 1.92 (95% CI 1.29–2.82, p = 0.009). There were also increased odds of PPH with type I diabetes: 2.83 (95% CI 1.45–5.30, p = 0.001), type II diabetes: 2.14 (95% CI 1.15–3.82, p = 0.012), twin delivery: 3.20 (95% CI 2.11–4.81, p ≤ 0.001), cesarean delivery: 5.66 (95% CI 4.53–7.09, p ≤ 0.001), and assisted vaginal delivery: 3.12 (95% CI1.95–4.88, p ≤ 0.001). Infants of mothers with PPH had high odds of NICU admission (CI = 1.34–2.07, p < 0.001) and hypoxic ischemic encephalopathy (CI = 1.64–7.14, p < 0.001). Conclusion: Our findings confirm previous literature that preexisting and pregnancy-related hypertension, diabetes mellitus, multiple gestation, cesarean delivery, and assisted vaginal delivery are important predictors of PPH. In addition, we found that neonates of mothers with PPH had more adverse outcomes. These results may help to inform clinical care as rates of PPH continue to rise in the United States.